The Relationship between Pain and Vascular Function Biomarkers in Dysmenorrheal University Students - Njoku, Uche Chinedu; Amadi, Peter Uchenna; Agomuo, Emmanuel Nnabugwu; Bhebhe, Michael (Chonnam National University Medical School and the Chonnam University Research Institute of Medical Sciences, 2022)
Our aim was to establish if the secretion of contactin 1 (CNTN-1), a widely researched pain biomarker correlates with the severity of dysmenorrhea and circulating levels of vascular cell adhesion molecule 1 (VCAM-1) and angiotensin II (ANG-II). This study was a longitudinal randomized clinical study that involved 95 female students between 17-25 years. The control participant group were students who, without medications, had not experienced dysmenorrhea, while the inclusion criteria were primary dysmenorrhea without medications. Data was collected using demographic questionnaires that also contained the Numeric Rating Scale (NRS-11), while blood samples were collected for analysis of CNTN-1, VCAM-1 and ANG-II by ELISA. The participants' mean BMI's across the four pain strata were between 16.60-38.43 kg/m2 and in addition to age and menarche, showed no correlation to either the NRS-11 scale (r=-0.01214) or their CNTN-1 levels (r=0.009622). The severe dysmenorrhea group showed statistically higher (p<0.0001) and positive correlation to systolic (r=0.7304) and diastolic (0.6588) blood pressures. The contactin 1 levels (7.00-55.70 ng/mL) increased with higher menstrual pain and as the pain increased, so did the mean VCAM-1 and ANG-II levels (p<0.0001). A positive linear correlation (r=0.9691) was observed between the NRS-11 scale of the participants and their CNTN-1 activities while the CNTN-1 levels positively correlated with their VCAM-1 (r=0.9334) and ANG-II (r=0.8746) secretion. In summary, the severity of dysmenorrheal pain elevates the contactin 1 levels which affects their vascular health and blood pressure.